Community Empowerment Through Rice Thresher Technology Innovation in Realizing Post-Harvest Efficiency and Local Food Security in Dharmasraya Regency - Refdinal, Refdinal; Adri, Junil; Putri, Lili Dasa (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This community service program is motivated by the fact that the people of Jorong Pinang Gadang still face various obstacles in managing agricultural products, especially in the post-harvest stage. The limitations of the tools and technology used are still the main obstacles in increasing agricultural efficiency and productivity. From an economic perspective, the income of the community largely depends on agricultural products, especially from the sale of grain. However, due to the limitations of post-harvest technology, the results obtained often experience shrinkage due to loss of grain in the threshing process. In addition, the selling price of grain which tends to fluctuate makes it difficult for farmers to obtain stable profits. This service aims to increase the efficiency of the rice threshing process and stimulate interest in rice farming among farmers, especially in Jorong Pinang Gadang, Nagari Koto Padang, Kabupaten Dharmasraya. The stages of the activity include: (1) stages starting from field surveys, (2) identifying problems, (3) determining solutions, (4) making designs, (5) making tools, (6) testing tools, (7) demonstrations, (8) handover of tools and, (9) evaluation and monitoring. This training successfully improved post-harvest efficiency for farmers and achieved local food security for the community in Nagari Koto Padang. The innovative rice thresher technology has increased farmers' productivity, both in terms of harvest quality and economics. Furthermore, the community has gained a better understanding of how to effectively manage a farmer group to achieve shared goals. Keywords: Training, innovation in rice thresher technology, post harvest efficiency, food security